PENINGKATAN MOTIVASI DAN HASIL BELAJAR SISWA PADA MATERI TARI KREASI MELALUI PROJECT-BASED LEARNING BERBANTUAN APLIKASI TIKTOK - Diah Purwandar (SENDIKRAF Jurnal Pendidikan Seni dan Industri Kreatif, 2021)
The aim of the current research project is to enhance students’ learning motivation and their ability in developing creative dance choreography design through the employment of projectbased learning model assisted by TikTok application for 36 (thirty-six) eleventh graders of SMA Negeri 5 Yogyakarta. Classroom Action Research using Kemmis and Targart model (1988) was adopted in this study, in which there are four components in its design, namely planning, action, observation, and reflection. Data were collected through observation with its field notes, documentation, questionnaires, interviews, and product assessment, and were analysed using qualitative descriptive technique. The result of the study demonstrates that the implementation of project-based learning assisted by TikTok application can enhance students’ motivation and their ability indicated by their learning achievement in developing choreography design of creative dance materials.